1984
DOI: 10.1136/bjo.68.12.869
|View full text |Cite
|
Sign up to set email alerts
|

Subretinal neovascularisation in eyes with localised inferior posterior staphylomas.

Abstract: SUMMARY We report seven cases of subretinal neovascularisation with inferior posterior staphyloma. The upper border of the shallow staphyloma, detected by B-mode echography, invaded the macular area, and there was a neovascular net at the edge of the staphyloma. Three of the cases showed chorioretinal atrophy at the upper edge of the staphyloma in the same location as the neovascular net. Our cases were identical to those of subretinal neovascularisation in high myopic eyes in which the rupture of Bruch's memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…The authors hypothesised that in each case, the sharp change in contour seen at the upper edge of the staphyloma may cause localised chorioretinal degeneration with secondary disruption of Bruch's membrane and subsequent CNV when the macular area is involved. 3 Quaranta et al 4 reported one case where multiple choroidal neovascular membranes developed along the inner edge of a macular staphyloma with pigmentary disturbance and focal chorioretinal atrophic patches in the macular region in a patient with pathological myopia. Based on this observation, the authors suggested that the edge of a staphyloma where the choriocapillaris is well preserved was an important transitional zone associated with an increased risk of chorioretinal changes and choroidal neovascular membrane formation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesised that in each case, the sharp change in contour seen at the upper edge of the staphyloma may cause localised chorioretinal degeneration with secondary disruption of Bruch's membrane and subsequent CNV when the macular area is involved. 3 Quaranta et al 4 reported one case where multiple choroidal neovascular membranes developed along the inner edge of a macular staphyloma with pigmentary disturbance and focal chorioretinal atrophic patches in the macular region in a patient with pathological myopia. Based on this observation, the authors suggested that the edge of a staphyloma where the choriocapillaris is well preserved was an important transitional zone associated with an increased risk of chorioretinal changes and choroidal neovascular membrane formation.…”
Section: Discussionmentioning
confidence: 99%
“…Probably in this area there is a greater stretching of choroid and retina which promotes the development of the atrophy. Moreover, it has been suggested that choroid and retina when bending abruptly on the edge of the ectasia can became involved in local degenerative processes which may lead to the choroidal neovascularization [15].…”
Section: Discussionmentioning
confidence: 99%
“…This complication was already described in some patients with tilted disc syndrome [4,7,12,14,15] and it generally develops in the inferotemporal edge of the ectasia. It is possible, as has already been noted, that in this area marked alterations of retinal pigment epithelium, Bruch's membrane and choriocapillaris are produced, thus promoting the development of choroidal neovascularization [12,15]. Moreover, at least in some patients, it is possible that this complication is an age-related disciform macular degeneration, rather than a neovascularization secondary to the myopic astigmatism of the fundus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an inferior staphyloma is often associated with this syndrome and severe complications such as choroidal neovascularization (CNV) can occur when the border of the staphyloma lies across the macula 47. This CNV usually shows a classic pattern on fluorescein angiography (FA) resulting in significant visual loss.…”
Section: Introductionmentioning
confidence: 99%